EKSPLORASI GAYA BELAJAR SISWA DALAM PROSES PEMBELAJARAN DI SEKOLAH - Talitha Salma Ashma Aulia; Salsabila; Elza Wydia Rohmah; Nabila Fitriani; Djoko Nugroho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to explore variations in students learning styles and theirimplications for the effectiveness of learning in fifth grade at Nurjali IslamicElementary School. The background of this study is based on the importance ofadapting learning methods to individual learning styles to improve learningoutcomes and motivation. Using a descriptive qualitative approach, data werecollected through the VARK (Visual, Auditory, Reading/Writing, and Kinesthetic)learning style questionnaire and semi-structured interviews with 13 purposivelyselected students. The results showed that students have diverse learning styles,namely visual (5 students), auditory (4 students), kinesthetic (3 students), andreading/writing (1 student). The findings also showed that students apply theirlearning styles in daily activities and that understanding learning styles leads tomore effective learning strategies. Adapting teaching methods by teachers tostudents learning styles has been shown to increase participation, motivation, andunderstanding in the learning process. This study recommends the importance ofadaptive learning approaches and the use of educational technology to supportdiverse learning styles in elementary school environments.